The Wine Industry & the COVID-19 Pandemic - Sergio Canavati; Matthew Bauman; Damien Wilson (Wine Business Journal, 2020)
When faced with extreme uncertainty and disruption, firms with superior knowledge and skills can not only identify more opportunities, but they can also envision how they will successfully exploit them. Firms that have developed the relevant knowledge, skills, and capabilities are more likely to act on perceived opportunities because they possess the expert schemas needed to focus on the most relevant information in the environment, process this information faster and more efficiently, and make decisions based on industry best practices. Despite the benefits of prior knowledge, deep expertise can also cause cognitive entrenchment leading experts to dismiss radically innovative and possibly disruptive ideas that fall outside the industry’s dominant paradigms.